Farnesoid X receptor ‐ a molecular predictor of weight loss after vertical sleeve gastrectomy?. (26th March 2019) - Scott, F.; Elahi, S.; Adebibe, M.; Parampalli, U.; Mannur, K.; Góralczyk, A.; Sanger, G. J.
Summary: Objective: To determine the expression of the bile acid receptor, farnesoid X (FXR), in human gastric mucosa and investigate correlations between expression and body‐mass index (BMI) and in patients with obesity, with changes in weight and BMI following vertical sleeve gastrectomy (VSG). Methods: Human gastric mucosa was obtained from normal/overweight individuals (macroscopically‐normal tissue following surgery for malignancy) or from patients with obesity (VSG). The expression of FXR and its isoforms (FXRα, FXRβ) were examined by quantitative PCR and compared with the G protein‐coupled bile acid receptor, GPBA. In patients with obesity, changes in BMI and weight loss were determined following VSG. Results: FXRα was the predominant isoform in normal/overweight individuals. FXR expression was higher in patients with obesity but GPBA receptor expression was unchanged. For those with obesity ( n = 19), no correlation was found between FXR expression and change in Body‐Mass Index (BMI)/month or weight loss/month, taken 3 ± 1 months after surgery, or in BMI or weight at surgery. Conclusions: Obesity is associated with increased FXR expression in the gastric mucosa. The findings are preliminary but suggest that this increase in FXR expression is a consequence of obesity, rather than its cause.